Genetic diversity of white yam (Dioscorea rotundata Poir) accessions maintained in tissue culture and cultivated in field using Simple Sequence Repeat (SSR) Markers and Morphological Characterization - Gabriel, A.; Agre, P.; Edemode, A.; Okon, A.E.; Bhattacharjee, Ranjana; Koyer, D. de (Academic Research Publishing Group, 2021)
Dioscorea rotundata is a staple food crop for millions of people in the tropical and subtropical regions. In vitro germplasm conservation is a very useful tool in yam improvement strategies but very little is known about the genetic integrity and stability of in-vitro conserved yam plants. In this study, 42 accessions from in vitro and field populations were genotyped using 11 microsatellite markers and 23 morphological descriptors to assess variability within and between accessions. Out of the 23 morphological variables used, 13 were identified as most discriminate and were used to cluster the accessions into 4 clusters using the unweighted pair group arithmetic mean average (UPGMA). Accession maintained in field as well as in in-vitro showed high genetic similarity (R2 = 0.91, p-value: 1e-04). Out of the 42 accessions analyzed, nine accessions maintained in the field and in-vitro displayed different genetic profiles. This study provided basic information on the possible somaclonal variation of yam accessions maintained through in-vitro. Further study with advanced tools such as next-generation sequencing is required to elucidate the nature of the observed variation within clones.